Luminescent chiral molecular glasses by melt-quenching enantiopure BINAP - Krittametaporn, Nuttaporn; Ralle, Philipp; Dierks, Dorothea; Nelle, Christian; Vasa, Suresh K.; Kolodzeiski, Pascal; Linser, Rasmus; Steffen, Andreas; Henke, Sebastian (Technische Universität Dortmund, 2025)
Chiral organic glasses combine unique optical properties with the processing advantages of amorphous solids. Here, melt-quenching as a strategy for preparing optically active glasses from enantiopure BINAP (2,2′-bis(diphenylphosphino)-1,1′-binaphthyl), a pivotal ligand in asymmetric catalysis and for luminescent metal complexes is demonstrated. Thermal characterization reveals that only R-BINAP and S-BINAP, not rac-BINAP, form molecular glasses with glass transition temperatures near 100 °C. Pair distribution function analysis and circular dichroism confirm the retention of local structure and homochirality despite the loss of long-range order. Remarkably, the glassy state has a beneficial influence on the molecular optoelectronic properties relative to the crystalline state, resulting in an increase of the radiative rate constant by ≈30%, attributed to more favourable Franck-Condon factors. In addition, a highly unusual simultaneous enhancement of circularly polarized luminescence (CPL) by nearly an order of magnitude is observed, achieving dissymmetry factors |glum| approaching 10−2 that are competitive with the top-performing purely organic molecular chiral emitters reported to date. These findings establish melt-quenched chiral molecular glasses as promising platforms for advanced optoelectronic and photonic materials, combining exceptional chiroptical properties, strong luminescence, and processability without the constraints of crystallinity.
Advanced science
Keywords: amorphous materials; circularly polarized luminescence; melt-quenching; molecular glasses; optical materials; 540; Amorpher Festkörper; Lumineszenz; Zirkularpolarisation; Schmelzen; Quenching; Optischer Werkstoff